Evaluación de la degradación de metomil en efluentes mediante el uso de un catalizador de dióxido de titanio (TiO2) dopado con nitrógeno en la empresa Sygla Colombia LTDA (2019)
In the present work of degree was made the synthesis of 12 catalysts of titanium dioxide doped with nitrogen in which as precursors of nitrogen and titanium made use of urea and titanium isopropoxide ,where a factorial design of 3^2 was carried out in which the molar proportion of N / Ti was varied between 0.0, 0.2, 0.4 and 0.6 to evaluate with influence of nitrogen in the photocatalysts; in addition to this the different Ni / T ratios were subjected to three different temperatures of 450 °, 550 and 650 ° C.